Resistance of Concrete and Cement to Chemical and Aggressive Environments - Egamberdiev Murad Saidovich; Hakimov Sherzod Hamzayevich; O`lmasov Suxrobbek Xurshid o`g`li (International Journal on Orange Technologies, 2021)
The resistance of the cement mortar to aggressive influences, when exposed to air, lime becomes denser due to gas formation in the air, the durability of the garage erected in the building. It has also been found that exposure to harmful exhaust gases increases, usually in wet conditions.